KNS‐760704 [(6R)‐4,5,6,7‐tetrahydro‐N6‐propyl‐2, 6‐benzothiazole‐diamine dihydrochloride monohydrate] for the Treatment of Amyotrophic Lateral Sclerosis - Gribkoff, Valentin K. (CNS Neurosci Ther, 2008)
Developing effective treatments for chronic neurodegenerative disorders such as amyotrophic lateral sclerosis (ALS) has proven extremely difficult. ALS is universally fatal, characterized by progressive weakness due to the degeneration of upper and lower motor neurons, and leads eventually to respiratory failure which is the usual cause of death. Only a single treatment has been approved, the modestly effective nonspecific neuroprotectant Rilutek® (riluzole; 2‐amino‐6‐(trifluoromethoxy)benzothiazole). KNS‐760704 [(6R)‐4,5,6,7‐tetrahydro‐N6‐propyl‐2,6‐benzothiazole‐diamine dihydrochloride, RPPX], a synthetic amino‐benzothiazole with demonstrated activity in maintaining mitochondrial function, is being developed as a treatment for ALS. It has proven to be effective in multiple in vitro and in vivo assays of neuroprotection, including the G93A‐SOD1 mutant mouse model; however, its specific mechanism of action remains unknown. The potential of KNS‐760604 as a treatment for ALS was first suggested by studies showing that its optical enantiomer, Mirapex®[(6S)‐4,5,6,7‐tetrahydro‐N6‐propyl‐2,6‐benzothiazole‐diamine; pramipexole dihydrochloride; PPX], a high‐affinity agonist at dopamine D2, D3, and D4 receptors, exhibits important neuroprotective properties independent of its dopamine receptor agonism. In cell‐based assays, both RPPX and PPX reduce the production of reactive oxygen species (ROS), attenuate the activation of apoptotic pathways, and increase cell survival in response to a variety of neurotoxins. However, PPX has limited utility as a clinical neuroprotective agent because the drug concentrations required for neuroprotection would likely produce unacceptable dopaminergic side effects. RPPX, on the other hand, while possessing the same neuroprotective potential as PPX, is a much lower‐affinity dopamine receptor agonist and may therefore be more useful in the treatment of ALS. This review will examine the data supporting the hypothesis that the RPPX may have therapeutic potential for the treatment of neurodegenerative disorders including ALS. In addition, we will briefly review recent preclinical data in support of RPPX, and discuss the current status of its clinical development.